Morphosemantic Analysis Skills Among Digital Native Non-Arabic Speakers - Adawiah, Siti Robiatul; Sopian, Asep; Nursyamsiah, Nunung (Ukazh: Journal of Arabic Studies, 2024)
This study aims to determine the ability of Arabic morphosemantic analysis on digital natives who are not native Arabic speakers. The research method used is descriptive quantitative with percentage-based analysis. Data were collected through an open-ended multiple-choice test that was structured based on morphosemantic indicators. The validity of the test instrument has been confirmed by Arabic morphosemantics experts. The study involved 34 digital native Arabic students, selected through a purposive sampling technique. The results show that the morphosemantic analysis ability of digital native non-Arabic speakers is generally considered insufficient, with a percentage of 49.2%. The ability in the aspects of word derivation and shighat is classified as moderate with a percentage of 67.6% and 65.7% respectively, while the ability in the aspects of affixes, word roots, semantic aspects, and wazan is categorized as "very poor" with a percentage of 44.7%, 42.1%, 37.2%, and 36.4% respectively. This study concludes that the morphosemantic analysis ability of digital native non-Arabic speakers is still at a deficient level, and effective strategies need to be developed to improve it Penelitian ini bertujuan untuk mengetahui kemampuan analisis morfosemantik bahasa Arab pada digital native yang bukan penutur asli Arab. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan analisis berbasis persentase. Data dikumpulkan melalui uji pilihan ganda terbuka yang disusun berdasarkan indikator morfosemantik. Validitas instrumen uji telah dikonfirmasi oleh ahli morfosemantik bahasa Arab. Penelitian melibatkan 34 mahasiswa bahasa Arab digital native, dipilih melalui teknik purposive sampling. Hasilnya menunjukkan bahwa kemampuan analisis morfosemantik digital native non penutur Arab secara umum tergolong kurang, dengan persentase 49.2%. Kemampuan dalam aspek derivasi kata dan shighat diklasifikasikan sebagai sedang dengan persentase masing-masing 67.6% dan 65.7%, sementara kemampuan dalam aspek imbuhan, akar kata, aspek semantik, dan wazan dikategorikan sebagai “sangat kurang” dengan persentase masing-masing 44.7%, 42.1%, 37.2%, dan 36.4%. Kesimpulan dari penelitian ini adalah bahwa kemampuan analisis morfosemantik digital native non penutur Arab masih memiliki tingkat yang kurang, dan strategi yang efektif perlu dikembangkan untuk meningkatkannya.